Kesesuaian Wisata Snorkeling dan Diving di Gusung Perlang Perairan Perlang Bangka Tengah - Robi Gunawan; Sudirman Adibrata; Andi Gustomi (Universitas Bengkulu, 2023)
ABSTRAK Gusung Perlang is located in Perlang Village, Central Bangka Regency. Gusung Perlang has underwater potential, namely coral reef ecosystems that becomes a tourist attraction in which the unique shape, color, and diversity of the biota with high selling value. This study aims to determine the value of the tourism suitability index, the carrying capacity of the snorkeling, and diving tourism area in the east Gusung Perlang waters. Moreover, the process of sampling is carried out in August 2021 at Gusung Perlang, Central Bangka Regency. The method of this study uses purposive sampling. Coral reef data is collected using the UPT (Underwater Photo Transect) method, reef fish using the visual census method and the time swim method. In addition, the data analysis is based on the tourism suitability index (IKW) matrix. The results of the Snorkeling Tourism Suitability Index (IKW) show that the location is suitable for station 1 (78.95%), station 3 (78.95%) and station 5 (77.19%), the location is conditional status in station 2 (70.18%). ) and station 4 (70.18%). The results of the tourism suitability index (IKW) calculation for diving show that the location is suitable for station 3 (77.78%), the location is conditional status in station 1 (72.22%), station 2 (62.96%), station 4 (62.96). %) and station 5 (74.07%). Keywords: Suitability, Gusung Perlang, Snorkeling, Diving